Physiotherapy management of patients with major chest trauma: Results from a global survey. (April 2020) - Aswegen, Heleen van; Reeve, Julie; Beach, Lisa; Parker, Romy; Olsèn, Monika Fagevik
Aim: Major chest trauma is associated with significant morbidity and mortality. Management of patients with major chest trauma includes pain relief, ventilatory management, surgical fixation and early rehabilitation to improve both short- and long-term outcomes. Physiotherapy is widely considered an integral component of the multidisciplinary trauma team and aims to improve respiratory status and reduce the sequelae associated with immobility and reduced physical function. Despite this there is scarce evidence describing or investigating physiotherapy interventions and how these practices vary worldwide. The aim of this study was to ascertain the current physiotherapy management of patients having sustained major chest trauma and to investigate how such practices varied internationally. Methods: A purpose designed online survey was administered to a group of experienced physiotherapists who work in the field of trauma. Results: Response rate was 51% ( n  = 49) and respondents represented all five continents. Respondents reported focussing on active coughing ( n  = 46, 96%, r  = 0.5, p  = 0.98), body positioning ( n  = 43, 94%, r  = 0.7, p  = 0.41), deep breathing exercises ( n  = 44, 94%, r  = 0.8, p  = 0.66) and early mobilisation ( n  = 47, 98%, r  = 1, p  = 0.64). Ambulation in hospital was reported to be common ( n  = 46, 98%, r  = 0.2, p  = 0.99) but rehabilitation to address longer term sequelae following hospital discharge was reported to be rare ( n  = 4, 8%). Conclusion: This survey has highlighted those practices used by physiotherapists worldwide which aim to address the complications associated with major chest trauma. Having established global practice, the study provides a platform for future research investigating the efficacy of such interventions in improving both short- and long-term outcomes for patients following major chest injury.